Pemetaan Daerah Potensi Longsor Menggunakan Analisis Fault Fracture Density Pada Data DEMNAS Di Wilayah Cisarua, Kabupaten Bandung Barat, Jawa Barat - Silmi Afina Aliyan; Totok Doyo Pamungkas; Kusnahadi Susanto; Putri Aprilia Ayesha (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2023)
The Cisarua area is located in the northern part of Bandung City and is one of the sub-districts in West Bandung Regency and has steep topography in several locations, giving rise to the potential for landslides. The eastern region is part of the Lembang Fault which is still active in the North Bandung area. The potential for landslides related to the geological structure in this area can be identified by looking at the lineament patterns of the valleys, the presence of lithological offsets and others. The geological structure that developed in the Cisarua area was identified based on the results of analysis of satellite imagery data and the National Digital Elevation Model (DEMNAS) to identify the presence of geological structures and determine the direction of the dominant force. This study aims to determine the distribution of potential landslides in the Cisarua area using the Fault Fracture Density (FFD) method. Linearity analysis is estimated using the Fault Fracture Density (FFD) method. This method produces an analysis based on the straightness of the ridges and valleys around Cisarua which is then processed using a rosette diagram and interpreted as the dominant lineament trending west-east and northeast- southwest, this dominant lineament corresponds to the direction of the Lembang Fault. The lineament density level value describes a weak zone in the rock which creates the potential for landslide hazard. The weak zone in red indicates that the study area has a high landslide hazard potential, which is red, and the light green color indicates that the study area has a low landslide hazard potential. The potential for landslides in the study area is spread more in areas close to regional geological structures such as faults when compared to other areas. This pattern indicates that the presence of geological structures has an influence on the occurrence of landslides in potential areas.